Penny Postcard of the Oxnard Plaza - United States Post Office::::::
The image of the plaza and pagoda in downtown Oxnard became a popular image for penny postcards. This particular image provides a view from the top of the Oxnard Hotel. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.